(untitled) (Journal of Hama University, 2021)
The aim of this study was : isolate and characterize the N 2 -fixing rhizobia from chickpea root nodules using biochemical and molecular methodologies. The research was carried out in the laboratory of bacterial plant diseases in the Faculty of Agriculture-Damascus and in the glass house of the National Commission of Biotechnology for the agricultural season 2019-2020. plant samples were collected from different locations of AS-Swaida governorate, Syria. A total of 40 isolates were obtained. Inoculated Chickpea seedlings with the previous rhizobial isolates were grown in pots containing N-free medium. Results showed that Only 26 isolates formed root nodules . The biochemical tests indicated that the isolated bacteria belong to the family of Rizobiaceae (gram, spore and oxidase negatives and catalase positive), and they were able to use sugars (e.g., xylose, maltose, fructose, galactose, sucrose and mannitol) as sources of carbon. Also, they metabolizes glucose but not lactose. Some isolates decompose starch and others dissolve gelatin. On the other hand, the molecular tests showed that, of 26 isolates 23 isolates were belonged to Mesorhizoium genus